2020
DOI: 10.21037/jtd.2020.01.52
|View full text |Cite
|
Sign up to set email alerts
|

Heart dose and coronary artery calcification in patients receiving thoracic irradiation for lung cancer

Abstract: Background: Thoracic irradiation (TIR) is associated with an increased risk of coronary artery disease (CAD) and coronary-related death. Lung cancer patients receive considerable doses of TIR, making them a high-risk population that may benefit from post-therapy surveillance. Coronary artery calcium (CAC) is a known biomarker of CAD development and may serve as a useful indicator of disease progression in this population. We hypothesized greater CAC progression in lung cancer patients subjected to higher whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A report from Korea revealed an increased risk of de novo malignancy after percutaneous coronary intervention (PCI) compared to age- and sex-matched control patients who had not undergone PCI [8] . Of note, the study showed that the risk for lung and hematologic cancers was higher than that for other types of cancer [7] . Conversely, in patients with established cancer, the treatment for malignancy may have adverse effects on the genesis and progression of CAD [13] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A report from Korea revealed an increased risk of de novo malignancy after percutaneous coronary intervention (PCI) compared to age- and sex-matched control patients who had not undergone PCI [8] . Of note, the study showed that the risk for lung and hematologic cancers was higher than that for other types of cancer [7] . Conversely, in patients with established cancer, the treatment for malignancy may have adverse effects on the genesis and progression of CAD [13] .…”
Section: Discussionmentioning
confidence: 89%
“…A recent meta -analysis showed that patients with cancer had a 1.5-fold increased risk of developing AF compared to those without cancer [4] . Additionally, cancer survivors have been found to have an increased risk of developing CAD [6] , [7] . Moreover, a previous study found a bidirectional association between the presence of CAD and an increased risk of death in patients with cancer [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Although pre-existing factors may affect the risk for developing CAD and cancer, in patients with established cancer, the treatment for their malignancy may also have adverse effects on the genesis and progression of CAD. Radiation, which is used in the treatment of various types of cancers, has been shown to increase the risk for ischemic heart disease ( 102 , 103 , 104 ). In one study, patients who received thoracic radiation for lung cancer had progression in coronary artery calcium, a known predictor of CAD, compared with those who did not ( 103 ).…”
Section: Common Links Between Cancer and Atherosclerotic Heart Diseasementioning
confidence: 99%
“…Radiation, which is used in the treatment of various types of cancers, has been shown to increase the risk for ischemic heart disease ( 102 , 103 , 104 ). In one study, patients who received thoracic radiation for lung cancer had progression in coronary artery calcium, a known predictor of CAD, compared with those who did not ( 103 ). Various classes of cytotoxic chemotherapy have been known to cause cardiotoxicity, cardiomyopathy, and vascular toxicity, which may contribute to increased atherosclerotic risk ( 105 ).…”
Section: Common Links Between Cancer and Atherosclerotic Heart Diseasementioning
confidence: 99%
“…Several small single-center studies suggest that baseline CAC might help identify subclinical ASCVD and predict CV events in these patients ( 45 , 46 , 47 ). Although there are limited data, there may be a role for CAC surveillance in these patients as it may demonstrate ASCVD disease progression related to RT ( 43 , 48 ) ( Figure 2 ). Cardiac CT has the ability to characterize atherosclerotic plaques and show features related to vulnerability; however, there are no data yet regarding the relationship of baseline plaque vulnerability, RT exposure, and outcomes.…”
Section: Role Of Cardiac Ct In the Assessment Of Coronary Artery Disease In Cancer Patients And Survivorsmentioning
confidence: 99%